K-AR DATING OF QUATERNARY VOLCANICS: METHODOLOGY AND INTERPRETATION OF RESULTS - Chernyshev I.V.; Lebedev V.A.; Arakelyants M.M. (My University, 2006)
The K-Ar method and its modifications play a unique role in the geochronology of young volcanic rocks, which has important fundamental and economic aspects. This method provides an opportunity for dating Quaternary rocks, from the oldest (1-2 Ma) to the most recent ones (<30 ka). this paper discusses physical and geochemical prerequisites for the use of k-ar method in solution problem. key factor providing favorable proportions radiogenic nonradiogenic 40Ar for the K-Ar system in volcanic rocks is the low solubility of argon (0.n-0.0n ppb) in silicate melts and crystallizing rocks and minerals. The sources and controlling factors of errors in the K-Ar dating of young rocks were evaluated in detail. The main analytical problem in the K-Ar dating of young rocks is concerned with the conditions and methods of measurements of very low (0.0n-0.00n ppb) contents of radiogenic 40Ar accompanied by much higher (by a factor of 3-10 or even more) contents of nonradiogenic 40Ar. The main stages in the development of the K-Ar method in Russia and other countries that provided a solution to this problem are described. We describe the analytical mass spectrometer system and method designed in the Institute of Geology of Ore Deposits, Petrography, Mineralogy, and Geochemistry, Russian Academy of Sciences, which allowed us to carry out for the first time in Russia systematic studies on the geochronology of Quaternary volcanics up to late Pleistocene-Holocene age. The main characteristics of the method are the absolute sensitivity of measurements (5 × 10-3 A/Torr) and background signal levels for argon isotopes (3 × 10-3 ng 40Ar and 1 × 10-5 ng 36Ar). The problems of excess radiogenic argon and variations in the initial 40Ar/36Ar ratio in young volcanics are discussed. The results of an investigation of the distribution of K-Ar isotopes among various constituents of young volcanics and the corresponding approach to the choice of material (geochronometer) for analysis are presented. This approach is illustrated by the example of geochronological results for three volcanic centers of the Caucasus differing in the time of occurrence and duration of the active phase: Elbrus, Samsari, and Aragats. A tentative regional time scale was proposed for Neogene-Quaternary magmatic events. This scale generalized the available data for the Greater and Lesser Caucasus and embraces the period from the late Miocene (8.5 Ma) to the late Neopleistocene-Holocene (<35 ka). An interesting feature of the young magmatism of the Caucasus is the synchronous occurrence of distinctive types of volcanic activity in particular volcanic areas. An important prognostic aspect related to the proposed time scale of the young magmatism of the Caucasus is the evidence that the most recent stage of volcanic activity, the youngest occurrences of which were dated at a few thousands to tens of thousands of years, is not yet finished. © Pleiades Publishing, Inc., 2006.
Keywords: Holocene; Pleistocene; Miocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен